PANDANGAN HUKUM ALI AS-SHOBUNI TENTANG PERCERAIAN - Desri Ari Enghariano (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
In this era of covid-19, divorce does not only happen to ordinary muslim household or celebrities. But also happens to the household of scholars who become public figures for the people. There is even a famous cleric who has dropped three divorces on his wife and there is also a popular cleric who divorced his wife in a relatively short marriage age, so that these problem has implications for the emergence of a negtive stigma against them. The fact is that for some people, divorce is the last alternative to end marriage. According to them, divorce is something that is taboo, disgraceful, and embarrassing. Evem though the scholars have explained that divorce is permissible ini Islam. Even under certain conditions divorce is a remedy, solution and them main choice, not the last alternative.One of the contemporary scholars who is concerned with examinig the issue of sharia law on divorce is Muhammad Ali al-Sabuni in his bokk Tafsir Verses of Law. There foe, this research will describe Ali al-Sabuni’s legal views on divorce; in the form of the etymological meaning and terminology of divorce, the legal basis fo divorce, conditions for divorce, kinds of divorce, the period od iddah of the wife after divorce, about three divorces, and the wisdom of divorce. The method used in this research is thematic method. The results of this research explain the meaning of divorce is ending marital status. The legal basis for divorce is the Qur’an, hadis, and ijma’. It is permissible to get a divorce if there is no harmony, the marriage is defiled, the spouse suffers from infertiliy, and infectious diseases. The are two kinds of divorce; namely raj’i and ba’in. The iddah of a wife who is not pregnant and still menstruating is three times sacred, the iddah of a pregnant wife is until she gives birth, and the iddah of a wife who has not menstruated or is monopause is three months